2020
DOI: 10.1088/1757-899x/997/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of permeability variation with the compression of soft reticulated foams

Abstract: The resistance to flow of imbibed fluids in soft porous structures subjected to compression can be a solution for impact attenuation. The mechanism, named ex-poro-hydrodynamic (XPHD) lubrication, is based on permeability variation with porosity, which, at its turn, depends on the compression degree of the porous structure. A literature survey revealed scarce information regarding the permeability of compressed reticulated foams or 3D fiber-based structures, used in XPHD applications. Moreover, the permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the last decades, theoretical ( [11], [12]) and experimental results ( [13], [14]), have shown that using porous and deformable materials, imbibed with fluids, greatly increases their impact damping capacity making the evaluation process of the material's permeability variation with compression level an activity of great importance. The evaluation of this variation has been possible with the use of complex experimental devices [15] and has proved to be an useful and thorough approach, but also time and resource consuming.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, theoretical ( [11], [12]) and experimental results ( [13], [14]), have shown that using porous and deformable materials, imbibed with fluids, greatly increases their impact damping capacity making the evaluation process of the material's permeability variation with compression level an activity of great importance. The evaluation of this variation has been possible with the use of complex experimental devices [15] and has proved to be an useful and thorough approach, but also time and resource consuming.…”
Section: Introductionmentioning
confidence: 99%